2017
DOI: 10.1097/md.0000000000007171
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase 1 expression is correlated with poor prognosis in breast cancer

Abstract: Breast cancer (BC) is one of the most common cancers worldwide, and is a major cause of death in women. Aldehyde dehydrogenase 1 (ALDH1) is a marker of stem cells and cancer stem cells, and its activity correlates with the outcome of various tumors, including BC. This study aimed to analyze the relationship between ALDH1 expression and clinicopathological characters in BC and the prognostic significance of ALDH1.We used quantitative reverse-transcription PCR (qRT-PCR) to detect ALDHA1 mRNA levels in 25 fresh f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
(43 reference statements)
0
18
1
Order By: Relevance
“…42,43 Domenic et al 44 reported that SOX9 expression may maintain human breast luminal progenitor cells, and may be associated with more aggressive tumours in BC. 45 The results of this study indicate that ALDH1A1 may be used not only as a CSC marker, but also as a prognostic and predictive marker, in BC. The protein expression of ALDH1A1 was more frequent in the highly proliferative (luminal B and TNBC) tumours, which suggests that ALDH1A1 may contribute to cell proliferation and tumorigenesis of BC.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…42,43 Domenic et al 44 reported that SOX9 expression may maintain human breast luminal progenitor cells, and may be associated with more aggressive tumours in BC. 45 The results of this study indicate that ALDH1A1 may be used not only as a CSC marker, but also as a prognostic and predictive marker, in BC. The protein expression of ALDH1A1 was more frequent in the highly proliferative (luminal B and TNBC) tumours, which suggests that ALDH1A1 may contribute to cell proliferation and tumorigenesis of BC.…”
Section: Discussionmentioning
confidence: 67%
“…The downstream genes of the retinoic acid pathway are also involved in the differentiation and proliferation of tumour cells. 45 The study results demonstrate that high expression of ALDH1A1 at both protein and mRNA levels has a positive association with poor prognostic features. Fei et al 39 concluded that ALDH1A1 predicts patient outcome in TNBC.…”
Section: Discussionmentioning
confidence: 68%
“…Additionally, when we included ALDH1A1 expression in the signature, EpCAM high VIM low ALDH1A1 high , its outcome prediction potential power was improved, remarking the need for the study of more cells markers besides EpCAM. In addition to its association with therapy failure, ALDH1A1 expression in tissue samples has been related to poor prognosis in different BC subtypes [63][64][65][66], and its expression in CTCs has also been linked with worse outcome in BC patients [23,26,28,32,67]. Likewise, Keup and colleagues suggested that the use of novel agents to attack BC stem cells, like salinomycin and a new synthetic curcumin analog against Aldehyde Dehydrogenase 1 (ALDH1), could be promising in patients with ALDH1+ CTCs [27].…”
Section: Discussionmentioning
confidence: 99%
“…Standard chemotherapies (e.g., taxanes) have been shown to enrich the population of CICs in TNBC [ 7 , 8 , 9 ]. These surviving CICs are implicated in generating chemotherapy-resistant, recurrent, and metastatic disease [ 1 , 3 , 10 ]. Therefore, there is a clinical need to develop novel, targeted approaches that kill both differentiated TNBC cells and CICs, particularly in recurrent and metastatic lesions, to improve the outcomes for patients with TNBC.…”
Section: Introductionmentioning
confidence: 99%